The effects of buprenorphine/naloxone maintenance treatment on sexual dysfunction, sleep and weight in opioid use disorder patients - Baykara, Sema; Alban, Kubra (Elsevier Ireland Ltd, 2019)
Opioid use disorder is a growing social problem. Different agents are used in the treatment of this disorder. One of these agents is buprenorphine / naloxone combination that includes buprenorphine and naloxone in a ratio of 4:1. Although used successfully in opiate maintenance treatment, buprenorphine / naloxone could have some side effects that might affect the treatment. The present study aimed to examine the effects of buprenorphine /naloxone opiate maintenance treatment on sexual dysfunction, sleep and bodyweight in patients diagnosed with opioid use disorder and to draw the attention of clinicians to the adverse effects of the treatment. The study group included 107 inpatients who were diagnosed based on The Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5) and received treatment for opioid use disorder. On admission to the hospital and at the end of the 4th month, a Sociodemographic and Clinical Data Form, the Pittsburgh Sleep Quality Index (PSQI) and the Arizona Sexual Life Scale (ASEX) were applied to all patients. Patients were weighed, and their weight was recorded on the day of admission to the hospital and at the end of the 4th month. The data recorded at the beginning and during the treatment of the same group were compared. The mean age of 107 patients was 24.55 +/- 4.27. Overall ASEX scores were 12.98 +/- 4.33 before treatment and 15.03 +/- 6.61 at 4 months (p < 0.001). The mean patient bodyweight was 63.86 +/- 8.78 kg before the treatment and 68.49 +/- 8.65 kg at the 4th month of the treatment (p < 0.001). Total PSQI scores were 8.87 +/- 3.53 before the treatment and 6.85 3.29 at the 4th month of the treatment (p < 0.001). The study findings demonstrated that after 4 months of buprenorphine /naloxone treatment, total ASEX scores and bodyweight of the patients increased and total PSQI scores decreased. These results demonstrated that sexual problems and bodyweight of the patients increased after the buprenorphine /naloxone treatment and sleep-related problems decreased, albeit still prevalent. These potential side effects should be included with other information about buprenorphine that is given to patients as they may influence interest in starting or continuing treatment.
Keywords: Opioid-related disorders; Drug side effects and adverse reactions; Opiate maintenance treatment; Sexual health; Sleep